Impact Of International Sanction On Foreign Organizations' Productivity & Activities In Iran A Case Study In United Nation - Mekanik, Sasan (2009)
This study analyzes the impact of US sanction on Iran's economy after a comprehensive introduction of United Nation in Iran. The author also find out the important success factors, strength and opportunity, on UN activities in Iran as well as enhanced strategy planning to overcome threats and convert weakness leading to achieve the highest performance and program delivery.